Competitiveness Analysis of the Tourism Sector in Azerbaijan and the Clustering Problem - AHMADOV, Fariz; MIRZAYEVA, Gulnar; MAMMADOV, Ilkin (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
With the globalization phenomenon accelerating around the world the level of development among countries is increasing steadily. When the examples of successful clusters in the world are examined, technological partnership goals, competitive advantage and creating a strong supply chain, to create synergy and importance given to cluster initiatives which aimed innovation is increasing. So while developed countries are now showing the benefits of clusters, it is now being implemented by developing countries. In increasing and sustaining of the competitive power of the regions, sectors are more interested in clusters. The aim of this study is to mobilize local potentials in the non-oil sectors of Azerbaijan is revealed the implementation of regional development policies in the tourism sector in our country.  Despite the development of clustering policies in the world, it can be said that implementation in our country is late. The advantages that the cluster provides to the businesses it hosts will encourage the development of the tourism sector in our country. Implementation of the cluster phenomenon is expected it will help to the elimination of the dependence of oil prices of oil-based economy, to increase the income of the country and to the prosperity of the people.  In the context of this qualitative study, the general situation of the tourism sector in Azerbaijan was analyzed, competitiveness of tourism is examined with diamond model and clustering situation was investigated.